E-036 Predicting Flow Diverter Deployments and Clinical Validation. (29th July 2016) - Chong, B; Babiker, H; Kalani, Y; Baccin, C; Mortensen, M; Levitt, M; McDougall, C; Frakes, D; Albuquerque, F
Abstract : Introduction: Flow diverters (FDs) are sized to the recipient vessel during pre-treatment planning. However, sizing can be challenging because of large changes in vessel curvature and diameter. Further, FDs can elongate by more than 50% of their labeled length after deployment, which complicates sizing. Significant complications can result from over- or under- sized devices. Here we present a finite element (FE) modelling approach for evaluating FD size and compare that approach to clinical deployments to determine its accuracy in predicting device length, diameter, and apposition. Methods: Ten patient cases treated with the pipeline embolization device were acquired from two hospitals. Pre- and post- treatment CT image data were segmented then reconstructed to form computational models of the devices and vessels. A library of pipeline FE models, which was previously validated against physical devices, was used to simulate deployment of the same devices into the pre-treatment vessels. The pipeline models were first navigated via a virtual microcatheter to the landing zones observed in the post-treatment vessels. A "push-pull" algorithm was then used to simulate device unsheathing. Three post-deployment metrics were compared: device apposition to the vessel wall along the vessel centerline, device diameter along the stent centerline, and device length. Results: Simulated and clinical deployments showed good agreement both qualitatively and quantitatively (Figure 1 ). Simulations captured regions where the device poorly apposed to the vessel wall and poorly covered the aneurysm neck. Mean errors between simulated and clinical deployments (as a percentage of the clinical value) were less than 5% for device length and 9% for device apposition and diameter. Conclusion: FE simulations captured post-deployment FD shape and apposition. Less than a 9% mean error was found between simulated and clinical deployment metrics. These results provide additional support for the use of FE for evaluating device size during pre-treatment planning. Disclosures: B. Chong: 4; C; Endovantage, LLC. H. Babiker: 4; C; Endovantage, LLC. Y. Kalani: None. C. Baccin: None. M. Mortensen: 5; C; Endovantage, LLC. M. Levitt: None. C. McDougall: None. D. Frakes: 4; C; Endovantage, LLC. F. Albuquerque: 4; C; Endovantage, LLC.